Change Management in Improving the Pedagogic Competence of Lecturers in Higher Education - Idariyanty; Edi Kusnadi; Trio Dika Kurniawan (Journal of Educational Management Research, 2025)
This study investigates the role of change management in enhancing the pedagogical competence of university lecturers. It addresses the growing need for educational institutions, particularly Islamic universities, to adapt to evolving educational demands and improve teaching quality through effective change management strategies. A qualitative research design was used, combining interviews, document analysis, and direct observation for data collection. The findings reveal that implemented change management initiatives have positively impacted lecturers’ pedagogical skills, leading to improved teaching methods, curriculum innovations, and more flexible instructional practices. Despite these positive outcomes, challenges such as limited training opportunities and insufficient collaboration with other academic institutions remain. The study highlights the importance of strategic planning and ongoing change management in improving pedagogical competence and recommends establishing comprehensive training programs and more substantial collaborative efforts with external academic partners.